Kat2a and Kat2b Acetyltransferase Activity Regulates Craniofacial Cartilage and Bone Differentiation in Zebrafish and Mice - Rwik Sen; Sofia A. Pezoa; Lomeli Carpio Shull; Laura Hernandez-Lagunas; Lee A. Niswander; Kristin Bruk Artinger (Journal of Developmental Biology, 2018)
Cranial neural crest cells undergo cellular growth, patterning, and differentiation within the branchial arches to form cartilage and bone, resulting in a precise pattern of skeletal elements forming the craniofacial skeleton. However, it is unclear how cranial neural crest cells are regulated to give rise to the different shapes and sizes of the bone and cartilage. Epigenetic regulators are good candidates to be involved in this regulation, since they can exert both broad as well as precise control on pattern formation. Here, we investigated the role of the histone acetyltransferases Kat2a and Kat2b in craniofacial development using TALEN/CRISPR/Cas9 mutagenesis in zebrafish and the Kat2ahat/hat (also called Gcn5) allele in mice. kat2a and kat2b are broadly expressed during embryogenesis within the central nervous system and craniofacial region. Single and double kat2a and kat2b zebrafish mutants have an overall shortening and hypoplastic nature of the cartilage elements and disruption of the posterior ceratobranchial cartilages, likely due to smaller domains of expression of both cartilage- and bone-specific markers, including sox9a and col2a1, and runx2a and runx2b, respectively. Similarly, in mice we observe defects in the craniofacial skeleton, including hypoplastic bone and cartilage and altered expression of Runx2 and cartilage markers (Sox9, Col2a1). In addition, we determined that following the loss of Kat2a activity, overall histone 3 lysine 9 (H3K9) acetylation, the main epigenetic target of Kat2a/Kat2b, was decreased. These results suggest that Kat2a and Kat2b are required for growth and differentiation of craniofacial cartilage and bone in both zebrafish and mice by regulating H3K9 acetylation.